Idiosyncratic risks, bailout, and financial crisis: A copula approach - Wang, Daphne; Nguyen, Khoa Huu (Global Business & Finance Review (GBFR), 2015)
EconStor is a publication server for scholarly economic literature, provided as a non-commercial public service by the ZBW.

U.S. oil company stock returns and currency fluctuations - Mollick, Andre; Nguyen, Khoa H (Managerial Finance, 2015)
Purpose The purpose of this is paper is to pay a closer look at the 2008-2009 financial crisis (and its aftermath) and analyzes stock returns of nine major US oil companies as well as the oil and gas sector under daily data from January 1992 to April 2012. Design/methodology/approach The authors adopt the arbitrage pricing theory model to examine the relationship between stock returns and their influences including oil price return, yield spreads, and US dollar index return. The authors also provide a test for structural changes in each regression model of return series to capture for multiple breaks. To examine the asymmetric effect of oil price returns on stock returns, the authors separate oil price returns series into two series: positive changes in oil price and negative changes in oil price. Findings The authors find stock returns of oil companies as well as the oil and gas sector are positively affected by oil prices and have stronger effects in the downward direction. Interestingly, The authors find the effects of oil price movements on stock returns increase over time. The authors examine the possibility that investors wishing to hedge against a weakening USD invest in US oil companies and find that more than half of these companies benefit from a weaker USD against the JPY, while all strongly benefit from a weaker USD against major currencies. Originality/value The authors employ daily data for two-decade period including the last global financial crisis. Due to the long-term period covered in this study, sequential Bai-Perron tests are used to detect structural breaks of stock return series. In addition, the data-dependent procedures result in good specifications throughout with white-noise processes in almost all cases.
Keywords: Exchange rates; Oil companies; Oil prices; Stock returns; USA; dept.fin

What explains the change in a firm’s idiosyncratic volatility after a dividend initiation? - Desai, Chintal A.; Nguyen, Khoa H (Managerial Finance, 2015)
Purpose The purpose of this paper is to identify three (maturity, agency, and information) effects that help explain the change in idiosyncratic volatility after a firm initiates a dividend. Design/methodology/approach The paper uses a cross-sectional analysis where the standard errors are adjusted for heteroskedasticity. As for robustness check, the authors perform two-stage analysis to control for potential self-selection bias. The authors also control for 2003 Dividend Tax Cut effect, matching-firm volatility, and confounding events. Findings Using a sample of 688 dividend-initiating firms for a period of 1977 to 2010, the authors find evidence consistent with the hypotheses based on the maturity, agency, and information effects. The volatility changes upon the dividend initiation can be reliably explained by the changes in profit volatility and free cash flow per total assets, and whether the firm consummated a stock split prior to the dividend initiation. The information effect is also found to be economically significant. Originality/value By studying a firm’s decision to initiate a dividend and its impact on the change in its volatility, the research helps contribute to the payout policy and volatility literatures.
Keywords: Dividend initiation; Idiosyncratic volatility; dept.fin

U.S. stock markets and the role of real interest rates - Huang, Wanling; Mollick, André Varella; Nguyen, Khoa Huu (The Quarterly Review of Economics and Finance, 2016)
Using weekly data from January 3, 2003 to March 27, 2015, we examine the responses of U.S. stock returns (S&P 500, DJIA, and NASDAQ) to monetary policy, controlling for WTI oil prices and the value of the U.S. dollar (USD) against major currencies. Based on differences between the federal funds rate and inflation expectations, U.S. real interest rates have become continuously negative since January 28, 2009. Vector auto-regressions (VARs) suggest stronger linkages more recently and vine copula models identify the structure of dependence across these markets, which can help investors optimize portfolio diversification.
Keywords: Exchange rates; Oil prices; Real interest rates; U.S. stock markets; Vine copulas; dept.fin

Emerging market hedge funds: Analysis of security selection and market timing - Dutta, S. (Banking and Finance Review, 2012)
Recent studies have documented that it is only very recently that the Emerging Market Hedge Funds (EMHFs) have started mimicking the performance pattern of regular Hedge Funds. These findings therefore motivate us to analyze the market timing and security selection skills of EMHF managers. Rolling regression technique is employed to analyze the above mentioned issues on a time-varying dimension. The rolling market timing regression results suggest that the EMHF managers do not exhibit consistently superior security selection or market timing skills even in an up-market scenario. The static market timing models however, indicate significant outperformance due to superior security selection and significant underperformance due to perverse market timing for the EMHFs in general. Multifactor asset class regressions, using fund-level data, reaffirm the notion that the EMHFs mimic the performance pattern reported for mutual funds in the mutual fund literature. © 2012, Banking and Finance Review.
Keywords: Emerging market; Hedge Funds; Security selection; dept.fin; ⛔ No DOI found

Exceeding expectations: economic forecasts and underreaction to macroeconomic announcements - Birz, Gene; Dutta, Sandip (SSRN Electronic Journal, 2015)
The chapter traces the development of Orthodoxy by focusing on the Ecumenical Patriarchate of Constantinople and the Russian Orthodox Church in the early modern period. It is based on the premise that in both cases Orthodoxy faced three main challenges: imperial/political, intellectual, and financial. In both the Ottoman and the Russian empires, the Orthodox Church played important roles in the political, administrative, cultural, economic, ideological, and social lives of the Orthodox believers. Orthodoxy usually provided legitimizing ideological support to state authority, was forced to reckon with Western cultural and theological trends, and also proactively defended its economic interests. For most of the period, the Ecumenical Patriarchate and the Russian Orthodox Church maintained constant contacts, even in the face of mutual suspicions of each other’s motives. The chapter argues that early modern Orthodoxy proved adaptive, developed over time, and withstood the challenges it faced, ultimately keeping its symbolic capital largely intact.
Keywords: dept.fin

Are we overestimating REIT idiosyncratic risk? Analysis of pricing effects and persistence - Abugri, Benjamin A.; Dutta, Sandip (International Review of Economics & Finance, 2014)
This study uses a multifactor REIT-specific model to estimate and compare REIT idiosyncratic volatility vis-A-vis the same from the Fama-French three-factor model. Estimates of conditional idiosyncratic volatility and conditional betas obtained from a multifactor REIT-returns model and a bivariate EGARCH model respectively are found to be positively and significantly related with REIT returns. Consistent with Merton's (1987) predictions, we observe that larger REITs post higher average returns when idiosyncratic risk is introduced in cross-sectional regressions. Persistence of past market-risk does not appear to be short-lived and seems to have a lasting impact on future idiosyncratic volatility. We also observe mild evidence of persistence of past idiosyncratic risk, albeit short-lived, thereby suggesting that past idiosyncratic risk has a short-term impact on future idiosyncratic risk. Published by Elsevier Inc.
Keywords: Conditional betas; Idiosyncratic risk; REITs; dept.fin

Emerging market hedge funds: are they managed like hedge funds? - Abugri, Benjamin A; Dutta, Sandip (Journal of International Financial Markets, Institutions and Money, 2013)
In this study, we investigate whether the performance of emerging market hedge funds (EMHFs) follow a pattern similar to that reported for advanced market hedge funds. In contrast to the pre-2007 period, our results for the post-2006 period showthat EMHFs exhibit performance patterns similar to those reported for hedge funds that focus on the developed markets. Unlike in the pre-2007 period, EMHFs in general do not exhibit significant exposure to specific asset classes in the post-2006 period. On a risk-adjusted basis, we find that EMHFs do not consistently outperform the benchmarks. The reported performance patterns may provide useful insights to both academics and portfolio managers.
Keywords: dept.fin; ⛔ No DOI found

Daytime vs. overnight trading in equity index futures markets - Dutta, Sandip; Sharma, Subhash C (Accounting and Finance Research, 2012)
Keywords: dept.fin; peer-reviewed

Testing trade-off and pecking order models of capital structure: does legal system matter? - Cotei, Carmen; Farhat, Joseph B; Abugri, Benjamin A (Managerial Finance, 2011)
Purpose – This paper aims to examine the link between financing patterns, information asymmetry and legal traditions in 37 countries during the 1990-2004 period. Design/methodology/approach – The analysis is based on three theories: the trade-off theory, pecking order hypothesis and market timing hypothesis. The authors test the predictions of these theories/hypotheses using regression analysis. The econometric method used is panel data with firm and country fixed effects. The authors develop a modified pecking order model which controls for short- and long-term debt level changes and simultaneously test the predictions of all theories. Findings – Consistent with studies for US firms, the results show that firms across all countries adjust toward the target leverage, but with significantly different rate. The long-term debt contribution in the rate of adjustment is 64 percent in common law countries and 51 percent in civil law countries. The ability of the model to explain changes in leverage ratios is higher in common law countries. The authors find support for market timing hypothesis but no support for pecking order of financing. These results support their conjecture that stronger investor protection, higher transparency and well-developed financial markets in common law countries reduce the cost of recapitalization. Research limitations/implications – The limitation of this study comes from lack of data availability to measure contract enforcement, transparency, and corporate governance variables. Future research can incorporate these variables to explain the differences in capital structure decisions across countries with different legal systems. Practical implications – The findings show that firms' capital structure decisions are not only a function of their own characteristics but also the result of legal and financial market development in which they operate. Originality/value – This is the first study that sheds light about rate of adjustment to optimal capital structure and pecking order of financing in 37 countries with different legal traditions and financial market developments. The authors are not aware of any other study that uses a modified pecking order model in an international context. © 2011, © Emerald Group Publishing Limited.
Keywords: Capital; Financial development; International capital structure; Legal systems; Pecking order theory; Trade-off theory; dept.fin; peer-reviewed

Ownership structure, non-interest income and bank risk in ghana - Abugri, Benjamin A; Osah, Theophilus Teye; Andoh, Samuel (Banking and Finance Review, 2016)
This study investigates the relationship between bank ownership structure, non-interest income and risk in an emerging market setting. Our analysis shows that the relationship between product diversification and bank risk is significantly influenced by asset size and ownership structure. In contrast to large banks, small banks are exposed to higher risk when the income share of non-traditional banking activities rise. We also find strong evidence of differences in risk exposure of banks to non-interest income after controlling for ownership structure. Private domestic and private foreign banks experience lower risk with higher non-interest income while the converse is true for public domestic banks. Furthermore, we show that the speed with which risk adjust to non-income activities is faster for domestic private banks than for foreign banks. These results could provide useful information to investors and regulators of banking institutions as they seek to reconcile the important issues of bank ownership structure, income diversification and size on the one hand with the level of risk exposure on the other hand. © 2016, Banking and Finance Review.
Keywords: Bank risk; Ghana; Non-interest income; Ownership structure; dept.eco; dept.fin; ⛔ No DOI found

Are hedge fund returns affected by media coverage of macroeconomic news? - Dutta, Sandip; Thorson, James (Studies in Economics and Finance, 2019)
Purpose: Extant literature suggests that the difficulty associated with the interpretation of macroeconomic news announcements by the market in general in different economic environments, might be the reason why most studies do not find any significant relationship between real-sector macroeconomic variables and financial asset returns. This paper aims to use a different approach to measure macroeconomic news. The objective is to examine if a different measure of a macroeconomic news variable, constructed from media coverage of the same, significantly affects hedge fund returns. Design/methodology/approach: The authors use a news index for unemployment, which is a real-sector variable, constructed from newspaper coverage of unemployment announcements and examine its impact on hedge fund returns. Findings: Contrary to the other studies that examine the impact of macroeconomic news on hedge fund returns, the authors find that media coverage of unemployment news announcements significantly affects hedge fund returns. Practical implications: Overall, this paper demonstrates that the manner in which the market interprets macroeconomic news announcements in different economic environments is probably a more relevant factor for hedge funds and is more likely to impact hedge fund returns. In conjunction with variables – constructed from media coverage of unemployment news announcements – that factor in the manner of interpretation, it is found that surprises also matter for hedge fund returns. This is an important consideration for hedge fund managers as well. Originality/value: To the best of the authors’ knowledge, this is the first study that examines the impact of media coverage of macroeconomic news announcements on hedge fund returns and finds significantly different results with real-sector macro variables. © 2019, Emerald Publishing Limited.
Keywords: Finance; Financial economics; dept.eco; dept.fin; peer-reviewed

Does the market know? Going concern opinion release and firm fundamentals - Huang, Jian; Yu, Han (International Journal of Accounting and Financial Reporting, 2019)
Using a significant auditing event-the going concern audit opinion-we investigate the market’s forecasting ability and the importance of firm fundamentals in predicting the going concern event. First, we find that the equity market signals the upcoming going concern announcement as early as 30 days in advance. Specifically, during the window of [-30, -1] leading up to the announcement, the excess returns to going concern firms are 9.98% worse than the matched distressed firms. Moreover, short sellers, a group of sophisticated investors, significantly increase their shorting activities during days before the release of the going concern opinions. Furthermore, we find that firm fundamentals, which are observable to the market, are significantly predictive to the issuances of going concern. These variables include a firm’s operating performance (return on assets and operating cash flows), equity market liquidity, stock momentum, and filing delay. Overall, our evidence supports the perception that the market can forecast the going concern opinion release and points out its possible channel as well.
Keywords: dept.fin; peer-reviewed

Firm risk and proxy fights: Evidence from SOX - Chen, Fang; Huang, Jian; Yu, Han (Accounting and Finance Research, 2018)
The Sarbanes Oxley Act of 2002 (SOX) is documented to curb executive risk-taking and firm risk. Utilizing SOX as an exogenous shock on firm risk, we find that proxy fight threats are positively related to a firm’s total risk and idiosyncratic risk. Specifically, although firm risk generally decreases post-SOX, high proxy fight threats mitigate this change in firm risk. We also find that although firms adopt more conservative policies such as decreasing their leverage and payout post-SOX, these changes are mitigated by proxy fight threats. In sum, our findings indicate that proxy fights act as an external disciplinary mechanism, encourage executive risk-taking, and increase firm risk.
Keywords: dept.eco; dept.fin; peer-reviewed

Stale economic news, media and the stock market - Birz, Gene (Journal of Economic Psychology, 2017)
I employ a classification of headlines from newspapers and wire services to examine whether stale macroeconomic news affects stock prices. Unlike with individual stocks, the cost of obtaining information about major economic releases is relatively low. Thus, stock prices should adjust to economic news announcements prior to their coverage in newspapers. I find statistically and economically significant relationship between stale news stories on unemployment and next week's S&P 500 returns. This effect is then completely reversed during the following week. These findings show that investors are affected by salient information and support the hypothesis that investors overreact to stale macroeconomic news reported in newspapers. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Attention; Efficient markets; Macroeconomic announcements; Media; Salience; dept.eco; dept.fin

Dynamic responses and tail-dependence among commodities, the US real interest rate and the dollar - Huang, Wanling; Mollick, André Varella; Nguyen, Khoa Huu (Empirical Economics, 2017)
Keywords: dept.fin

Examining the dynamic linkages of performance and volatility of REIT returns - Dania, Akash; Dutta, Sandip (The Journal of Wealth Management, 2017)
This article extends the literature on the financial performance of real estate investment trusts (REITs) by examining whether U.S. REIT returns are impacted by global REITs and other real estate subsectors, such as the U.S. Real Estate Index (USRE) and the U.S. Mortgage Finance Index (USMF). The authors also explore the issue of volatility transmission and the asymmetric effect of volatility spillover on U.S. REIT returns from innovations originating in other real estate subsectors and Global REITs. Results suggest that U.S. REITs are impacted by USRE and USMF returns. There is also evidence of volatility spillover from key real estate constituents-that is, USRE and USFM returns and global REIT markets. These results can be attributed to the changing dynamics of the real estate sector and the gradual integration of the global real estate sector as an asset class. These findings have strong implications for constructing global portfolios including REITs.
Keywords: dept.eco; dept.fin

Institutional ownership and the spillover effects of shareholder activism - Jory, Surendranath; Ngo, Thanh; Nguyen, Khoa Huu (International Journal of Corporate Governance, 2017)
Keywords: dept.fin